ANALISIS IMPLEMENTASI KEBIJAKAN PEMBERIAN PEMBEBASAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) PROVINSI DKI JAKARTA TAHUN 2024 DI UPPPD CEMPAKA PUTIH JAKARTA PUSAT - Wirano, Tito Prasetiyo; Permatasari, Mira (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
In connection with the problem of tax receivables and the amount of tax that must be paid by taxpayers, the DKI Jakarta Provincial Government issued a policy in the Regulation of the Governor of the Special Capital Region of Jakarta Number 16 of 2024 concerning the Provision of Relief, Reduction, and Exemption and Ease of Payment of Rural and Urban Land and Building Taxes in 2024. The purpose of this study is to analyze and evaluate the Implementation of the Policy for Granting Exemption of Rural and Urban Land and Building Taxes (PBB-P2) of DKI Jakarta Province in 2024 at UPPPD Cempaka Putih, Central Jakarta. The research approach used in this study is a qualitative approach. The results of this study show that the implementation of the policy of granting exemption from rural and urban land and building tax (PBB-P2) for DKI Jakarta Province in 2024 at UPPPD Cempaka Putih, Central Jakarta has not been able to run well even though the employee resources, infrastructure and budget are appropriate, the disposition of the attitude and commitment of employees who uphold the ASN code of ethics and the organizational structure that is in accordance with the Standard Operating Procedure (SOP) and authority based on position in the organizational structure has been running well, but there are shortcomings in the communication of the delivery of information received by taxpayers where the delivery is still uneven and unclear even though it has been done consistently